Questionnaire feedback from MBBS second year students about current examination trends and their opinion for perspective changes - Ahmed, Fazeel Zubair; Kudthni, Ravi Hanumanthappa (International Journal of Basic & Clinical Pharmacology, 2021)
Background: All subjects of MBBS do not have same examination pattern especially concerning to question paper pattern and distribution of marks. As a result, students are experiencing variety of examination patterns during their study. Neither is their uniformity of examination pattern throughout the country nor there is uniformity within a university. In such situation, it would be wise to take feedback from students which could help in redesigning the examination pattern. This study was done to collect students’ opinion regarding current examination methods and possible changes that might be required in existing assessment methods. Methods: Questionnaire based study was done on MBBS second year students of Viswabharathi medical college. Questionnaire consisted of 10 questions about examinations faced by the students. Each question had five options arranged according to 5-point Likert scale. Results: 99 students participated in this study. 51.52% students preferred having two essay questions and 42.42% preferred having one essay question in final theory exam. 52.53% preferred to have 40 marks as weightage of one paper. 50.51% supported having illustration-based questions in their final theory examinations. 79.80% stated that at least 30 days of preparation holidays are required for them before their final exams. 48.48% preferred having five very short answer questions. 48.48% stated that weekend tests conducted by their institute were helpful to them. 66.66% disagreed upon increasing number of questions in final examination. 63.63% agreed on having MCQ’s. 48.48% agreed on having viva voce during every internal examination. Consensus could not be reached upon frequency of institutional tests. Conclusions: This study highlighted certain shortcomings in medical education with respect to examinations. Weightage and number of questions might be increased marginally to have a uniform pattern. Question paper should have more very short answer questions and less essay questions. Illustration based questions should also be introduced. 30 days of preparation holidays must be given before final exams for self-study.